Governing Rural Water through Participation: A Policy Design Analysis of Indonesia’s PAMSIMAS Program - Bunga Alicia; Dewi Noor Azijah; Mochamad Faizal Rizki (Journal of Government Science Studies, 2026)
Rural water provision in Indonesia remains a persistent governance challenge, particularly because access, service continuity, and infrastructure maintenance depend not only on technical delivery but also on institutional design and local participation. PAMSIMAS has been widely promoted as a community-based drinking water and sanitation program, yet the way participation is designed as a policy mechanism for governing rural water services remains insufficiently examined. This article aims to analyze how participation is embedded in the policy architecture of Indonesia’s PAMSIMAS program and how it shapes the distribution of roles, responsibilities, and accountability among state and community actors. Using qualitative document-based policy design analysis, the research examines official policy documents, program guidelines, technical manuals, institutional reports, and relevant scholarly literature. The findings show that participation functions as a governance logic that connects community involvement, local ownership, shared contribution, institutionalized management, and service sustainability. However, participation also carries critical risks when community responsibility becomes a substitute for sustained state support. The analysis implies that effective rural water governance requires participatory mechanisms supported by durable public commitment, inclusive decision-making, technical assistance, affordability safeguards, and clear accountability structures.